Tribological characterisation of carbon nanotubes/ultrahigh molecular weight polyethylene composites: the effect of sliding distance. (10th September 2010) - Kanagaraj, S.; Mathew, M.T.; Fonseca, A.; Oliveira, M.S.A.; Simoes, J.A.O.; Rocha, L.A.
The tribological characterisation of metal-on-polymer (MOP) or ceramic-on-polymer (COP) couple is required to prevent osteolysis and loosening of the prosthesis which leads to subsequent failure of the implants. An attempt was made to enhance the tribological properties of ultrahigh molecular weight polyethylene (UHMWPE) by adding the carbon nanotubes (CNTs). The chemically treated CNTs were homogeneously mixed with UHMWPE using a ball milling process and the mixed raw materials were used to prepare a compression moulded sheet. Tribological characterisation of the test sample as a function of sliding distance was carried out in a tribometer using a ball on plate configuration. Different types of wear trend and friction coefficient were observed in polymer and nanocomposites. It was also observed that wear volume and wear coefficient decreases significantly with an addition of CNTs in the polymer and they follow a linear relation with sliding distance.